(untitled) (American Journal of Technology and Applied Sciences, 2025)
This article examines the key characteristics of the precious stone market (diamonds, rubies, sapphires, emeralds, etc.) as an asset class: liquidity, profitability, pricing factors, risks (price volatility, counterfeiting, regulatory and reputational risks), and prospects (growing demand for colored stones, the impact of lab- grown diamonds, sustainable development, and supply chain transparency). A review of empirical studies on profitability and volatility is provided, along with a discussion of practical recommendations for investors.